Failures in psychiatric treatment : the proceedings of the thirty-seventh annual meeting of the American Psychopathological Association, held in New York City, June 1947 - American Psychopathological Association; Hoch, Paul Henry, 1902-1964 (New York : Grune & Stratton, 1948)
"The present symposium is, to our knowledge, the first attempt to present a general review of therapeutic failures with different psychiatric methods of treatment. It is obvious that successful cases are easy to report and the hesitancy to do similarly with unsuccessful ones is understandable. But to admit failures is a sign of intellectual and emotional maturity. Psychiatry is young as a science, battling against great handicaps because of inexact methodology as compared with the exact sciences. Nevertheless, it has amassed a large body of knowledge and has today a secure place in medical therapeusis. It is mature enough to admit failures and to analyze their origins. We believe, therefore, that the present volume will contribute to the better understanding of the theory and praxis of psychiatric treatment. (PsycINFO Database Record (c) 2006 APA, all rights reserved)"--Foreword.
Includes bibliographies.
Keywords: Psychiatry -- Congresses; Psychiatry -- Congresses; Psychotherapy -- Congresses; Psychotherapy -- Congresses